2022
DOI: 10.1002/ange.202205453
|View full text |Cite
|
Sign up to set email alerts
|

2D MOF with Compact Catalytic Sites for the One‐pot Synthesis of 2,5‐Dimethylfuran from Saccharides via Tandem Catalysis

Abstract: One pot synthesis of 2,5‐dimethylfuran (2,5‐DMF) from saccharides under mild conditions is of importance for the production of biofuel and fine chemicals. However, the synthesis requires a multitude of active sites and suffers from slow kinetics due to poor diffusion in most composite catalysts. Herein, a metal‐acid functionalized 2D metal‐organic framework (MOF; Pd/NUS‐SO3H), as an ultrathin nanosheet of 3–4 nm with Lewis acid, Brønsted acid, and metal active sites, was prepared based on the diazo method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…The high-resolution TEM (HRTEM) images exhibited the distance between adjacent Zr 6 oxide clusters was 2.0 nm, which matched well with the corresponding modeled structural (20.4 Å) of NUS (Figure 1D). 10,19 The high-angle annular dark-field scanning TEM (HAADF-STEM) micrograph and elemental mapping confirmed that the Pd nanoparticle and SO 3 H groups are uniformly distributed on the catalyst surface (Figure S8). (Figure 1E).…”
Section: Conversion Of Saccharides To 25-dimethylfuranmentioning
confidence: 88%
See 2 more Smart Citations
“…The high-resolution TEM (HRTEM) images exhibited the distance between adjacent Zr 6 oxide clusters was 2.0 nm, which matched well with the corresponding modeled structural (20.4 Å) of NUS (Figure 1D). 10,19 The high-angle annular dark-field scanning TEM (HAADF-STEM) micrograph and elemental mapping confirmed that the Pd nanoparticle and SO 3 H groups are uniformly distributed on the catalyst surface (Figure S8). (Figure 1E).…”
Section: Conversion Of Saccharides To 25-dimethylfuranmentioning
confidence: 88%
“…15,16 Figure 4D summarize the conversions of disaccharides group. 10,19,53 To study the underlying mechanism, the comparative experiment of the non-acidic Pd/C and Lewis acidic Pd/NUS was conducted in glucose reaction. Under an N 2 atmosphere, the concentration of in situ-generated fructose is hard to be detected by high-performance liquid chromatography, because fructose is easily polymerized to humins without the mediation of Brönsted acidity.…”
Section: Hydrophobicity and Oleophilicity Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional (2D) nanomaterials with extraordinary physical and chemical properties have been attracting dramatic attention after the successful preparation of graphene from graphite in 2004. , In recent years, dramatic strides have been achieved in the field of 2D nanomaterials. As the burgeoning class of crystalline porous materials, metal–organic frameworks (MOFs) are composed of metal nodes/clusters and coordinating organic linkers. , 2D MOF nanosheets could combine the tunable structures of MOFs and the unique properties of 2D nanomaterials, making them exhibit great potential in many applications, for example, energy storage and conversion, catalysis, sensors, and biomedicine. , Compared with the fast development of 2D MOF nanosheets in many application fields, the crystallization process of 2D MOF nanosheets remains ambiguous. To date, the crystallization mechanism of MOFslargely drew experience from the classical nucleation and growth theory of conventional organic/inorganic compounds, in which the monomer was added into the crystals during crystal growth.…”
Section: Introductionmentioning
confidence: 99%
“…As the burgeoning class of crystalline porous materials, metal−organic frameworks (MOFs) are composed of metal nodes/clusters and coordinating organic linkers. 3,4 2D MOF nanosheets could combine the tunable structures of MOFs and the unique properties of 2D nanomaterials, 5 making them exhibit great potential in many applications, for example, energy storage and conversion, 6 catalysis, 7 sensors, 8 and biomedicine. 9,10 Compared with the fast development of 2D MOF nanosheets in many application fields, the crystallization process of 2D MOF nanosheets remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%